2011
DOI: 10.1007/s10948-011-1251-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CeO2-Cap Layer on the Texture and Critical Current Density of YBCO Film

Abstract: YBa 2 Cu 3 O 7 (YBCO) thin films have been fabricated on different textured CeO 2 -cap layers by pulsed laser deposition (PLD). The texture and critical current density J c of YBCO thin films have been systematically investigated. Both in-plane and out-of-plane textures of YBCO films and CeO 2 -cap films were characterized by X-ray diffraction (XRD). And the critical currents of YBCO films were measured by the conventional four-probe method. It was found that the texture and J c of YBCO films were largely depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…(3) where ∆M is the difference of magnetization at a field, in emu/cm 3 , a is the area of the inscribed circle, in cm and J is critical density in A/cm 2 . Figure 8 shows the plots of the current density J against the field in Tesla, at 77K it explains that the 50 pulses of the YBCO/CeO 2 in the multilayer gave highest J c which was about 4.1 MA/cm 2 this agrees with other report (Huang, Li, Wang, Qi, Sebastain, Haugan &Wang, 2017;Xu, Liu, Wang, Zhu, Zhu & Li, 2012;Lee, Kim, Park & Park, 1996;Feng, Zhang, Qu, Huang, Xiao, Zhu, Lu, Shi, &. Han, 2015) against the pure YBCO and we observed that the more CeO 2 was added in the multilayer the less the J c , and T c we got, and this did not affect its structural properties.…”
Section: Multilayer Deposition Of Ybco/ceosupporting
confidence: 86%
See 1 more Smart Citation
“…(3) where ∆M is the difference of magnetization at a field, in emu/cm 3 , a is the area of the inscribed circle, in cm and J is critical density in A/cm 2 . Figure 8 shows the plots of the current density J against the field in Tesla, at 77K it explains that the 50 pulses of the YBCO/CeO 2 in the multilayer gave highest J c which was about 4.1 MA/cm 2 this agrees with other report (Huang, Li, Wang, Qi, Sebastain, Haugan &Wang, 2017;Xu, Liu, Wang, Zhu, Zhu & Li, 2012;Lee, Kim, Park & Park, 1996;Feng, Zhang, Qu, Huang, Xiao, Zhu, Lu, Shi, &. Han, 2015) against the pure YBCO and we observed that the more CeO 2 was added in the multilayer the less the J c , and T c we got, and this did not affect its structural properties.…”
Section: Multilayer Deposition Of Ybco/ceosupporting
confidence: 86%
“…Aside from the thickness dependence of J c , there is also a limitation placed on the thickness at which such films could be grown (Uzun & Avci, 2014;Zhao, Iton & Goto, 2014;Sueyoshi, Kotaki, Fujiyoshi, Mitsugi, Ikegami & Ishikawa, 2013). (Huang, Li, Wang, Qi, Sebastain, Haugan, &Wang, 2017), reported the enhanced flux pinning properties of YBCO thin films with various pinning landscapes a magnetic nanocomposite of La 0.7 Sr 0.3 MnO 3 (LSMO))x (CeO 2 ) 1-x was incorporated into YBCO as either a cap layer or a buffer layer but the defect pinning and magnetic pinning are introduced in the systems giving the J c at 77K to be around 4.66MA/cm 2 (Xu et al, 2012), reported the influence of CeO 2 -cap layer on the texture and critical current density of YBCO film, here the found that the texture and J c of YBCO film were largely dependent on the texture of CeO 2 -cap layers under optimized deposition conditions, with the increase of the degree of in-plane and out-plane texture of CeO 2 -cap layers, there was a decrease in the Jc of the YBCO thin films from 4.23MA/cm 2 to 0.47MA/cm 2 . (Lee, Kim, Park & Park, 1996), agreed that addition of CeO 2 into YBCO will increase the critical current density to an extent at 77K, they reported 2x 10 4 A/cm 2 an increased by lowering the measuring temperature.…”
mentioning
confidence: 99%
“…A KrF excimer laser (LPX220, Lambda Physik Inc., Fort Lauderdale, FL, USA) with a wavelength of 248 nm was used for CeO 2 , YSZ, and YBCO film deposition, and the incident angle between the laser beam and the target surface was 45°. Detailed experiments were reported in other works [16,17]. From previous experiments [16], we obtained the samples of CeO 2 , YSZ/CeO 2 , and CeO 2 /YSZ/CeO 2 buffered NiW tapes.…”
Section: Methodsmentioning
confidence: 99%
“…The CeO 2 film is the most widely used buffer layer for YBCO films on both single crystal substrates and flexible metallic substrates due to the fact that it has a comparatively small lattice mismatch, a similar thermal expansion coefficient, and good chemical compatibility with YBCO at its high deposition temperature. [10,11] The ISTEC-fabricated CeO 2 cap layer by PLD on IBAD-Gd 2 Zr 2 O 7 has a high in-plane grain alignment and we call it the self-epitaxial PLD-CeO 2 cap layer. [12−14] Researchers have reported the enhancement of the in-plane grain alignment of the CeO 2 cap layer by optimization of deposition temperature and target density.…”
mentioning
confidence: 99%